Type VI Secretion Systems Present New Insights on Pathogenic Yersinia - Yang, Xiaobing; Pan, Junfeng; Wang, Yao; Shen, Xihui (Frontiers in Cellular and Infection Microbiology, 2018)
The type VI secretion system (T6SS) is a versatile secretion system widely distributed in Gram-negative bacteria that delivers multiple effector proteins into either prokaryotic or eukaryotic cells, or into the extracellular milieu. T6SS participates in various physiological processes including bacterial competition, host infection, and stress response. Three pathogenic Yersinia species, namely Yersinia pestis, Yersinia pseudotuberculosis, and Yersinia enterocolitica, possess different copies of T6SSs with distinct biological functions. This review summarizes the pathogenic, antibacterial, and stress-resistant roles of T6SS in Yersinia and the ion-transporting ability in Y. pseudotuberculosis. In addition, the T6SS-related effectors and regulators identified in Yersinia are discussed.